The Use of Mobile Legends to Facilitate English Narrative Writing Skills Development: Students' Perceptions - Qothrunnada, Ahmad Ilham; Asmiyah, Siti; Siraj, Taufik; Hasnawati, Lina (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mobile Legends, has been widely used in teaching and learning English. However, despite that, its impact on English narrative writing skills among students has not yet been explored. Thus, this study aims to explore students' perceptions regarding using Mobile Legends to enhance their English narrative writing skills. Fifteen students from a state Indonesian school in Malaysia participated in a qualitative study using questionnaires and interviews. The participants' responses were analyzed using a descriptive and descriptive approach. The results show that the game's characters and backgrounds provide a wealth of material for graphically illustrating story components and substantially enhance descriptive skills, narrative coherence, and linguistic structures. The positive responses from the participants suggest a burgeoning potential for incorporating mobile gaming into language education, fostering a deeper connection between students and language learning. The study provides valuable insights into the positive impact of gamification on language proficiency, offering educators an exciting avenue to explore in creating dynamic and effective learning environments